To study the acceptance of epidural analgesia for painless labor at a tertiary care centre - Gupta, Neena; Gupta, Sachidanand; Agrawal, Apurva; Agrawal, Shaily; Diwedi, Seema; Singh, Jyotsna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Epidural analgesia is a central nerve block technique achieved by injection of a local anaesthetic close to the nerves that transmit pain and is widely used as a form of pain relief in labor. Epidural analgesia is the most effective method of pain relief during labor. But unfortunately in India incidence of painless labor by epidural analgesia is very rare even in these days. The aim of our study was to study the acceptance of epidural analgesia at a tertiary care centre. Methods: The present study was conducted in department of obstetrics and gynaecology UISEMH, Kanpur over the period from May 2012 to May 2013. The study was conducted on 98 patients who were counselled regarding the adoption of epidural analgesia as painless labour and out of these 50 patients opted for epidural analgesia. Results: In our present study the acceptance was greater in primigravida (72.43%) as compared to multigravida (20%). In our society social reason was the common cause for non-acceptance in primigravida (87.5%). The majority of patients belonged to middle socioeconomic status (52%) and more number of educated patients opted for epidural analgesia. Conclusions: It was found that increased awareness can lead to increased acceptance of epidural analgesia.